2020
DOI: 10.3389/fonc.2020.01717
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Anti-cMet Antibody seeMet 12 Potentiates Sorafenib Therapy and Radiotherapy in a Colorectal Cancer Model

Abstract: Rational: cMet is abnormally regulated in gastrointestinal cancer, and is associated with increased invasiveness of the disease and poor overall survival. There are indications that targeted therapy against cMet, alone or in combination with additional cancer therapies, can help improve treatment outcome. Thus, in the present study we investigated the therapeutic efficacy of a novel cMet-targeting antibody therapy in gastrointestinal cancer models, and assessed potential augmenting effects in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Data from clonogenic assays from this study showed that HT29 cells treated with a combination of 2 Gy and seeMet 12 compound (c-MET inhibitor) had significantly reduced colony formation than 2 Gy monotherapy ( P < 0.001) (Ref. 53). This was potentiated when the radiation dose was escalated to 4 Gy ( P < 0.001) (Ref.…”
Section: Hallmark 3: Resisting Cell Deathmentioning
confidence: 79%
See 2 more Smart Citations
“…Data from clonogenic assays from this study showed that HT29 cells treated with a combination of 2 Gy and seeMet 12 compound (c-MET inhibitor) had significantly reduced colony formation than 2 Gy monotherapy ( P < 0.001) (Ref. 53). This was potentiated when the radiation dose was escalated to 4 Gy ( P < 0.001) (Ref.…”
Section: Hallmark 3: Resisting Cell Deathmentioning
confidence: 79%
“…Similarly, novel antibodies targeting c-MET acted synergistically with RT in CRC cell lines and in murine xenograft models (Ref. 53). Data from clonogenic assays from this study showed that HT29 cells treated with a combination of 2 Gy and seeMet 12 compound (c-MET inhibitor) had significantly reduced colony formation than 2 Gy monotherapy ( P < 0.001) (Ref.…”
Section: Hallmark 3: Resisting Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, abnormal expression of c-Met has been reported in a variety of cancers, such as CRC, non-small lung cancer, gastric cancer, and breast cancer (7)(8)(9)(10). In addition, c-Met over-expression is related to the proliferation, invasion, and angiogenesis of tumors (11,12). Crizotinib is a small molecule targeting inhibitor of diverse receptor tyrosine kinases (RTKs), such as c-Met, anaplastic lymphoma kinase (ALK), and ROS1 receptor (13).…”
mentioning
confidence: 99%